Selective Activation of G Protein-coupled Estrogen Receptor 1 Attenuates Atherosclerosis - Haider, Mohammad Z.; Sahebkar, Amirhossein; Eid, Ali H. (Current Medicinal Chemistry, 2024)
Atherosclerosis remains a leading contributor to cardiovascular disease-associated morbidity and mortality. Interestingly, atherosclerosis-associated mortality rate is higher in men than women. This suggested a protective role for estrogen in the cardiovasculature. These effects of estrogen were initially thought to be mediated by the classic estrogen receptors, ER alpha, and beta. However, genetic knockdown of these receptors did not abolish estrogen’s vasculoprotective effects suggesting that the other membranous Gprotein coupled estrogen receptor, GPER1, maybe the actual mediator. Indeed, in addition to its role in vasotone regulation, this GPER1 appears to play important roles in regulating vascular smooth cell phenotype, a critical player in the onset of atherosclerosis. Moreover, GPER1-selective agonists appear to reduce LDL levels by promoting the expression of LDL receptors as well as potentiating LDL re-uptake in liver cells. Further evidence also show that GPER1 can downregulate Proprotein Convertase Subtilisin/ Kexin type 9, leading to suppression of LDL receptor breakdown. Here, we review how selective activation of GPER1 might prevent or suppress atherosclerosis, with less side effects than those of the non-selective estrogen.
Keywords: cardiovascular disease